Assessment of Right Ventricular Function, Blood Lactate Levels, and Serum Peptidomics Profiles Associated With Mitral Valve Disease in Dogs - Petchdee, Soontaree; Yalong, Mona; Kaewnet, Methawee; Ithisariyanont, Burasarin; Padawong, Tanawat (Frontiers in Veterinary Science, 2022)
Background: Degenerative mitral valve disease is a common heart problem in dogs. The aims are to evaluate the relationships between right and left ventricular function, blood lactate concentrations, assess prognostic contribution, and investigate whether serum peptidomics profile could reveal markers or determine the stage in dogs with valve degeneration. Materials and methods: 93 dogs were evaluated in this study. Thirty-nine dog’s serum was collected and analyzed using matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS). The Kaplan-Meler curve was used to predict the outcomes of mitral valve disease. Follow-up was obtained by a questionnaire or telephone to determine a survival time. Results: The BUN: creatinine ratio, vertebral heart score (VHS), and left atrium: aorta ratio (LA: AO) were the independent predictors of cardiac mortality. Right ventricular systolic dysfunction was found in 50 % of dogs with mitral valve disease. Dogs with right ventricular dysfunction had a significantly higher incidence of lower fractional shortening and larger RV dimensions. The occurrence of right-sided dysfunction is proportionate to age and the degree of left ventricular dysfunction. High blood lactate concentrations were investigated in dogs with mitral valve disease stage C compared with stage B. The peptides such as Mitogen-activated protein kinase (MAPK), Kallikrein (KLK), and Tenascin-C (TN-C) appeared in the heart disease progression group. Conclusion: Right-hearted function assessment, blood lactate levels, and peptidomics analysis may help early detection and prognosis of this disease in dogs. Peptidomics profiles from this study demonstrate the possibility for prognosis indicators of heart valve degeneration.